STRATEGI MENGHADAPI TANTANGAN ARUS BUDAYA GLOBAL MELALUI PENDIDIKAN KARAKTER BERBASIS BUDAYA - Rulianto ruli; Ida Bagus Brata; Ida Bagus Nym Wartha (Jurnal Pendidikan dan Kebudayaan Missio, 2020)
This article was compiled based on the results of a study aimed at knowing and understanding the Strategy to Face the Challenges of Global Cultural Flow through Cultural Education Based on Culture. This study uses a qualitative method. Data obtained through observation, interviews, documentation, and literature study, in a natural setting. Data analysis was carried out through three activities simultaneously, namely: data reduction, data presentation, and conclusions or verification. The results of the study indicate that the world of education is currently facing the challenges of global cultural currents, namely the process and system of economic expansion of a transnational free market economy that has penetrated into various fields of life such as politics, religion, socio-culture, including education. In the era of openness marked by the dynamics of local, national, and global communities that have the potential to cause various impacts it is impossible to avoid. Therefore, it is important for a nation to have character and identity in the face of global cultural currents, in order to remain firmly established on the noble values ​​of the nation's culture. Culture-based character education can be used as an educational strategy and symbolic investment strategy accompanied by efforts to create a conducive social environment through a tri center of education (family, school, and community). Reviving local cultural values ​​in certain packages is one cultural approach to empowerment. Thus the revitalization of local cultural values ​​in the era of globalization plays an important role. This needs to be done considering the cultural behavior among children and adolescents has begun to change along with the growing pressure of global cultural currents.